Late gadolinium enhancement cardiac magnetic resonance imaging of ablation lesions after postinfarction ventricular tachycardia ablation: Implications for ventricular tachycardia recurrence. (4th February 2022) - Ghannam, Michael; Liang, Jackson; Attili, Anil; Cochet, Hubert; Jais, Pierre; Latchamsetty, Rakesh; Jongnarangsin, Krit; Morady, Fred; Bogun, Frank
Abstract: Background: Late gadolinium enhancement cardiac magnetic resonance (LGE‐CMR) imaging distinguishes between intrinsic postinfarction scar and radiofrequency ablation lesion related scar (dark core lesions [DCLs]) in patients with prior ventricular tachycardia (VT) ablation procedures. Objective: To combine LGE‐CMR and electroanatomic mapping data to describe the relationship between DCLs and recurrent VT among patients undergoing repeat ablations for postinfarction VT. Methods: Consecutive patients with repeat ablation for postinfarct VT with LGE‐CMR before the repeat procedures were studied. Prior ablation procedures and implantable cardiac defibrillator electrograms were analyzed to determine new versus previously documented VT. DCLs were identified on preprocedure LGE‐CMR and registered to electroanatomic maps. A control group of patients undergoing repeat ablation procedures without imaging was included. Results: Nineteen study patients and 14 control patients were followed for 2.6 (1.6–5.6) years (31 [94%] men, age 65.8 ± 8.4 years, ejection fraction 24.7 ± 10.3, p  > 0.10 for all). DCLs corresponded to unexcitable tissue during repeat procedures (area 22.4 ± 15.1 vs. 22.9 ± 16.8 cm 3, correlation coefficient = .93). Most VT target sites (39/50 [78%]) were in close proximity (<1 cm) to DCLs. Most DCL related VTs 32/39 (82%) were new VTs. Patients with LGE‐CMR imaging incorporated into their ablation procedures had improved 24‐month survival from VT (64% vs. 38%, log rank p  < 0.02). Conclusion: LGE‐MRI can identify prior ablation lesions corresponding to nonexcitable tissue during repeat ablation procedures for postinfarction VT. VT target sites are often located in close proximity to the DCL area that may function as a fixed border for reentry circuits. Registration of DCL from prior ablation may facilitate repeat ablation procedures.